Spatial Distribution and Biogeochemical Cycling of Dimethylated Sulfur Compounds and Methane in the East China Sea During Spring. Issue 2 (18th February 2019) - Zhai, Xing; Li, Jian‐Long; Zhang, Hong‐Hai; Tan, Dan‐Dan; Yang, Gui‐Peng
Abstract: The spatial distributions of dimethylsulfide (DMS), dimethylsulfoniopropionate (DMSP), dimethylsulfoxide (DMSO), and methane (CH4 ) were studied in the East China Sea during May 2017, and the possible controlling factors and biogeochemical cycling processes are discussed. The mean surface concentrations of DMS and CH4 were 10.66 and 9.93 nmol/L in the coastal area and 7.60 and 6.88 nmol/L in the open ocean, respectively. Horizontal and vertical profiles of the dimethylated sulfur compounds and CH4 were largely affected by different water masses, with enhancement observed in the coastal area. Significant correlations were found between CH4 and particulate DMSP ( r  = 0.609, p  < 0.01, n  = 42), and between CH4 and dissolved DMSO ( r  = 0.654, p  < 0.01, n  = 42). A dissolved DMSP (DMSPd ) spike experiment revealed that the bacterial communities had potential to utilize DMSPd, meanwhile producing CH4 under oligotrophic conditions. The average mixing ratio of atmospheric DMS was 109 ± 49 pptv. Variations of marine DMS and wind speed explained 23 and 40% of the variation in the mixing ratios of atmospheric DMS, respectively. The sea‐to‐air fluxes of DMS and CH4 were estimated to be 18.64 ± 14.92 and 13.85 ± 15.03 μmol m −2 d −1, respectively. Plain Language Summary: Some gases in the atmosphere can alter the environment and climate, such as dimethylsulfide (DMS) and methane (CH4 ). The oceans are an important source of DMS, and a nonnegligible source of CH4, especially the coastal and estuarine areas. DMS and CH4 emissions from the ocean to the atmosphere depend directly on their concentrations in the surface water. To know what factors control DMS and CH4 concentrations is therefore of great importance. In our study, the horizontal and vertical distributions of DMS, CH4, and related compounds were determined, and deck incubation experiments were carried out to assess the effects of biological activities on their cyclings. We also present the first analysis of the atmospheric DMS concentrations in the marine boundary layer above the East China Sea. We find that the DMS and CH4 concentrations were mainly influenced by the complex water masses, especially the freshwater input, and biological processes. Under some circumstances, dimethylsulfoniopropionate (DMSP), a ubiquitous compound in the seawater, is a precursor of both DMS and CH4 . Key Points: Spatial distributions of dimethylated sulfur compounds and CH4 were measured, and the controlling factors were discussed DMSP was used by bacteria for potential production of CH4 under certain conditions Atmospheric DMS concentrations were measured for the first time, and sea‐air fluxes of DMS and CH4 were estimated